KEMAMPUAN BERPIKIR KRITIS PADA SITUATION-BASED LEARNING - Rosi Rosmiati; Isrokatun Isrokatun; Dety Amelia Karlina (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
This study was conducted to determine the description of SBL learning on students' critical thinking skills. In learning the teacher has an important role to improve students' ability to construct knowledge independently. From the existing problems, students are accustomed to receiving knowledge without asking the problems found. Situation-based learning can facilitate problem-posing, problem solving and independent learning. Through the stages of SBL learning can make it easier to provide structured guidance to facilitate students through discussion as well as problem posing and critical thinking skills. This study uses a qualitative descriptive method with class IV research subjects. The instruments used are tests, observation guidelines and interviews. Qualitative data from observations and interviews obtained were reduced to draw conclusions. Then the quantitative data on critical thinking skills obtained are calculated on average and then the percentage is made to see the best results. The findings from this study SBL learning creates interactive learning, supports students in digging up information and solving problems. Then, SBL learning also has a good impact on students' critical thinking skills. Therefore, the description of SBL learning can be an alternative reference for teachers in increasing student potential and can create student-centered learning.